With freedom in our ears : histories of Jewish anarchism - Torres, Anna Elena; Zimmer, Kenyon, 1980- (University of Illinois Press, 2023)
"Jewish history and the history of anarchism have long marginalized Jewish anarchist thought and action. Anna Elena Torres and Kenyon Zimmer edit a collection of essays aimed at recovering the many rich strands of this lost past. The contributors introduce a range of perspectives while offering transdisciplinary research in areas like the history of radicalism, theology, women's history, and communications history. Jewish anarchism's multilingual nature helps us understand the impact of language politics on questions of cultural and ethnic identity. The contributions illuminate an ongoing engagement with non-Jewish radical cultures by looking at the Jewish anarchist press's passion for translating philosophy, political theory, and literature into the many native languages of its readers. The writers also reveal that Jewish anarchists drew from a matrix of secular, cultural, and religious influences--not all of them Judaic--to create anarchisms that ranged from mysticism to ethnically mixed, militantly atheist revolutionary cells"--